2015
DOI: 10.1080/15567036.2014.907374
|View full text |Cite
|
Sign up to set email alerts
|

The Influence of Inoculum to Substrate Ratio on the Biochemical Methane Potential of Fat, Oil, and Grease in Batch Anaerobic Assays

Abstract: Anaerobic digestion is one of the potential methods widely applied for organic waste recovery to produce biogas. In this study, biodegradability of fat, oil, and grease was tested in biochemical methane potential assays and the effects of substrate to inoculum ratio ranging from 0.2-4.0 were determined. The results indicated that fat, oil, and grease is feasible to produce methane (670 mL CH 4 gVS −1 ) and the ideal substrate to inoculum ratio range of 0.5-1.0 was determined. After 60 days of experiments, maxi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 35 publications
0
8
0
2
Order By: Relevance
“…However, for 0.457 at the lower mixing ratio (20-80%) and 0.462 at the higher mixing ratio (80-20%), the biogas ceased after 23 days, while the volume of methane production was slightly lower than that of the 0.25-0.3 Vs sub/ Vs inoculum range. This indicates that the amount of micro-organism required for an anaerobic reaction to take place is not enough for the biodegradation process [45,46]. Based on the highest methane yield produced as shown in Table 4, it could be considered that a Vs sub/Vs inoculum range of 0.25-0.3 is the ideal ratio for methane yield.…”
Section: Waste Analysis and Characterizationmentioning
confidence: 99%
“…However, for 0.457 at the lower mixing ratio (20-80%) and 0.462 at the higher mixing ratio (80-20%), the biogas ceased after 23 days, while the volume of methane production was slightly lower than that of the 0.25-0.3 Vs sub/ Vs inoculum range. This indicates that the amount of micro-organism required for an anaerobic reaction to take place is not enough for the biodegradation process [45,46]. Based on the highest methane yield produced as shown in Table 4, it could be considered that a Vs sub/Vs inoculum range of 0.25-0.3 is the ideal ratio for methane yield.…”
Section: Waste Analysis and Characterizationmentioning
confidence: 99%
“…S/I ratio is an indicator concerning the appropriate inoculum volume to provide for the required amount of microorganisms for the anaerobic reaction to startup. Thus, the used volume of inoculum influences the amount of produced methane [29]. In their study, Caillet et al [58] showed that the methane yield reaches its maximum for values of S/I ratio ranging between 0.6 and 0.9, and inhibitions occur when the ratio exceeds 1, due to volatile fatty acids accumulations during the degradation.…”
Section: Physicochemical Characterizationmentioning
confidence: 98%
“…For less degradable substrates, such as lignocellulosic organic matter, a ratio less than or equal to 1 can be applied [28]. Nazaitulshila et al [29] showed that it is necessary to carry out a BMP test before the designing of an anaerobic process in an actual reactor, due to the fact that each substrate and inoculums have been produced from different sources, and they differ in their characteristics.…”
Section: Inoculums To Substrate Ratio (Isr)mentioning
confidence: 99%
See 1 more Smart Citation
“…En este estudio a concentraciones de inóculo por debajo del nivel óptimo se tuvo un efecto negativo en la producción de biogás y el rendimiento de metano, lo cual puede atribuirse a que las reacciones de biodegradación no ocurrirán si la cantidad de microorganismos no es suficiente, afectando la producción de biogás (Nazaitulshila et al 2015).…”
Section: Efecto De La Concentración Inicial De Inóculounclassified